Monday

December 22, 2014

December 22, 2014

Posted by **Elle** on Thursday, May 9, 2013 at 1:54pm.

1/(tanx-secx) + 1/(tanx+secx) = -2tanx

- Trig -
**Steve**, Thursday, May 9, 2013 at 2:43pmrecall that

(a-b)(a+b) = a^2-b^2

sec^2(x) - 1 = tan^2(x)

put the fractions over a common denominator and watch the answer fall out.

**Answer this Question**

**Related Questions**

Trig - Verify the identity. (secx + tanx)/(secx - tanx) = (1 + 2sinx + sin(^2)x...

Trig - Verify the identity: tanx/secx-1=secx+1/tanx

precal - 1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-...

Math - I can't find the integral for (tanx)^(6)*(secx)^(2) I tried splitting up ...

precal - verify: tanx secx = -2tanx

Trig - verify the following identity: tanx+cotx/cscx=secx

precal - (1/tanx-secx))+(1/(tanx+secx))=-2tanx

Pre Calculus - (secx)/(tanx)+(cscx)/(cotx)=secx+cscx Please help me verify this ...

Precalculus - Complete the following identity secx-1/secx=? I have four multiple...

Math (Trig) a.s.a.p, thanks! - verify the identities: 1.) 2tanx-(1+tanx)^2 = -...